2022
DOI: 10.1101/2022.01.25.22269839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological Characteristics and Severity of Omicron Variant Cases in the Aphp Critical Care Units

Abstract: Importance Information about the severity of Omicron is scarce. Objective To report the respective risk of ICU admission in patients hospitalized with Delta and Omicron variants and to compare the characteristics and disease severity of critically ill patients infected with both variants according to vaccination status. Design Analysis from the APHP database, called Reality, prospectively recording the following information in consecutive patients admitted in the ICU for COVID-19: age, sex, type of variant, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…This supports the growing evidence of reduced disease severity among those infected with Omicron [2,48]. Results from similar studies in South Africa, the United States and France have also reported a reduction in LoS, risk of ICU admission and/or death among Omicron patients compared with Delta patients [912].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This supports the growing evidence of reduced disease severity among those infected with Omicron [2,48]. Results from similar studies in South Africa, the United States and France have also reported a reduction in LoS, risk of ICU admission and/or death among Omicron patients compared with Delta patients [912].…”
Section: Discussionsupporting
confidence: 74%
“…Results from similar studies in South Africa, the United States and France have also reported a reduction in LoS, risk of ICU admission and/or death among Omicron patients compared with Delta patients [9][10][11][12].…”
Section: Discussionmentioning
confidence: 77%
“…This supports the growing evidence of reduced disease severity among those infected with Omicron (2;4-8). Results from similar studies in South Africa, USA and France have also reported a reduction in the median LoS, risk of ICU admission and/or death among Omicron patients compared to Delta patients (9-12).…”
Section: Discussionmentioning
confidence: 75%
“…Given that the amino acid sequence of the S protein of the recombinant BA.2 virus that these authors tested is the same as that of the BA.2 isolate that we tested, differences at locations other than the S gene could have epistatic or independent effects that offset differences in the pathogenic potential of the S gene 44 . Omicron variants are less likely than Delta variants to be associated with pneumonia in human patients with COVID-19 45 . We observed that BA.2 infection in the lung was less pathogenic in mice and hamsters than SARS-CoV-2 strains from early in the pandemic (Figs.…”
Section: Discussionmentioning
confidence: 97%